Effective Demand-Driven Supply Chain Management and Long-run Stock Performance - Li, Xun; Wu, Qun; Holsapple, Clyde W. (Journal of Applied Business and Economics, 2017)
This paper examined the long-run stock price performance of firms with effective Demand-driven supply chain management (DDSCM). We used AMR’s “Supply Chain Top 25” ranking to obtain a sample of firms independently identified as top performing DDSCM firms. The results show that investing in the portfolio of top DDSCM firms can generate significantly positive abnormal returns after controlling for a variety of factors to discount alternative explanations. We also investigated buy-and-sell abnormal returns and found that investors can earn significantly positive abnormal returns by simultaneously buying a portfolio of top DDSCM firms and selling a portfolio of matching firms.